Crossing Enemy Lines in Ken Loach’s Ae Fond Kiss/Just A Kiss - Kristine Chick (Angles)
In the West, negative stereotypes of Muslims and Islam are not limited to the post-9/11 era, and surface not only in the media and non-fiction but also in literature, fine art, film, and children’s cartoons. This article focuses on depictions following 9/11, specifically on the ways in which the dominant image of the Muslim as ‘enemy’ can be subverted in film through an analysis of Ae Fond Kiss (dir. Ken Loach, 2004). It focuses on questions of identity, and the emergence of what social anthropologists such as Vertovec (1997) label ‘new ethnicities’ (the development of hybrid or syncretic cultural identities). The acknowledgement of new ethnicities can serve to counter facile negative stereotyping and the entrenched bias that sometimes permeate mainstream British media and culture.